2021
DOI: 10.3390/computation9030027
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pressure-Driven Electroosmotic Flow through Elliptic Cross-Sectional Microchannels with Various Eccentricities

Abstract: The semi-analytical solution for transient electroosmotic flow through elliptic cylindrical microchannels is derived from the Navier-Stokes equations using the Laplace transform. The electroosmotic force expressed by the linearized Poisson-Boltzmann equation is considered the external force in the Navier-Stokes equations. The velocity field solution is obtained in the form of the Mathieu and modified Mathieu functions and it is capable of describing the flow behavior in the system when the boundary condition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Hence, an increase in the eccentricity yields a lower volumetric flow rate. This result is well consistent with Numpanviwat's work [32]. When the slip flow phenomenon is applied, i.e., l = 0, Q * increases as an increase in the slip length.…”
Section: Effect Of the Eccentricity On Slip Flowsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, an increase in the eccentricity yields a lower volumetric flow rate. This result is well consistent with Numpanviwat's work [32]. When the slip flow phenomenon is applied, i.e., l = 0, Q * increases as an increase in the slip length.…”
Section: Effect Of the Eccentricity On Slip Flowsupporting
confidence: 91%
“…They concluded that considering the circular channel with the same perimeter instead of an elliptic channel is inappropriate. In 2021, Numpanviwat et al [32] proposed the mathematical model of transient combined pressure-driven and electroosmotic flow in an elliptic microchannel under the no-slip condition. The effect of the eccentricity of the channel cross-section was studied in two situations by fixing either the area or the perimeter of the cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two constants C arise in this equation for each fluid layer. Therefore, the boundary conditions for each liquid-liquid and solid-liquid interface must be applied to determine the values of C 2n−1 and C 2n , which are given in Equations ( 16)-( 18) and (21). Then, first the boundary condition in Equation ( 16) is applied into (24) for the fluid n = 1 at the interface placed at r = a, yielding…”
Section: Solution Methodologymentioning
confidence: 99%
“…where, D n and E n are integration constants, which will be found by implementing the boundary conditions from Equations ( 16) and ( 19)- (21) to Equation (56). First, by applying Equation (16) to Equation ( 56) corresponding to the fluid layer n = 1 at the interface placed at r = a, the following relationship is obtained:…”
Section: Steady-state Velocity Profilesmentioning
confidence: 99%
See 1 more Smart Citation